2020
DOI: 10.1371/journal.pone.0224056
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of pollen and resource limitation of fruit production in Vaccinium uliginosum and V. vitis-idaea in Interior Alaska

Abstract: Many recent studies assessing fruit productivity of plants in the boreal forest focus on interannual variability across a forested region, rather than on environmental variability within the forest. Frequency and severity of wildfires in the boreal forest affect soil moisture, canopy, and community structure at the landscape level, all of which may influence overall fruit production at a site directly or indirectly. We evaluated how fruit production in two boreal shrubs, Vaccinium uliginosum (blueberry) and V.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…Only some shoots became reproductive, and whether the shoots had formed an inflorescence or remained vegetative could not be determined at collection until late in the growing season (see Table S2 for number of reproductive shoots and primordia at each collection date). Vaccinium vitis‐idaea is less likely to flower when canopy cover is high (Parkinson & Mulder, 2020), and this is reflected in fewer dates on which reproductive shoots were collected in the shadiest sites (Table S1). Because in early June we could not distinguish between shoots without flower primordia that would not become reproductive and shoots with no primordia that would subsequently transition to flower initiation, we present values for June flowering shoots in figures but do not include this collection in the quantitative analyses of development.…”
Section: Methodsmentioning
confidence: 99%
“…Only some shoots became reproductive, and whether the shoots had formed an inflorescence or remained vegetative could not be determined at collection until late in the growing season (see Table S2 for number of reproductive shoots and primordia at each collection date). Vaccinium vitis‐idaea is less likely to flower when canopy cover is high (Parkinson & Mulder, 2020), and this is reflected in fewer dates on which reproductive shoots were collected in the shadiest sites (Table S1). Because in early June we could not distinguish between shoots without flower primordia that would not become reproductive and shoots with no primordia that would subsequently transition to flower initiation, we present values for June flowering shoots in figures but do not include this collection in the quantitative analyses of development.…”
Section: Methodsmentioning
confidence: 99%
“…Based upon wild blueberry, some of the mechanisms of decreased fruit set due to climate warming and increased precipitation are: reduced activity of bees during rainy days, reduction of the longevity of stigma viability during warm springs, faster rate of progression through the bloom period by the flowering clones (genetically unique individual plants), asynchrony between the emergence of wild bees and the early blooming clones, and increased blossom loss due to infection by Monilinia vaccinii-corymbosi (Reade) (the causal fungal organism of mummy berry disease) [15,26,68]. Parkinson and Mulder [2] also support our hypothesis that bog blueberry fruit set will be affected in a similar way that wild blueberry fruit set is by warming. In Alaska, USA, they found that bog blueberry exhibited a decline in fruit set in warmer lowland sites relative to cooler upland sites.…”
Section: Practical Implications Of Model Predictionmentioning
confidence: 99%
“…Bog blueberry (Vaccinium uliginosum L.), is a Eurasian and North American flowering plant species in the genus Vaccinium within the heath family [1,2]. The commercial value of bog blueberries comes from their antioxidant content, which is the highest of 40 common fruits and vegetables [3].…”
Section: Introductionmentioning
confidence: 99%